New Aspects of Malnutrition in Jakarta - W. A.F.J. Tumbelaka (Indonesian Pediatric Society, 1974)
The title of this paper is rather pretentious, since many of these socalled new aspects have been studied in other countries before in a more intensive way. However, in Indonesia they have received the attention of the medical world only in recent years. The purpose of this paper is to report on the present state of nutritional surveys and research. As a matter of fact it is not feasible to discuss all new aspects of malnutrition in this paper.